From Erasmus to Turing: What now for Study Mobility between the UK and the EU? Damage Limitation and New Opportunities - James, Cherry (Pécs journal of international and European law, 2021)
On 24th December 2020 the EU and the UK concluded the Trade and Cooperation Agreement and announced, contrary to widespread hopes and expectations, that the UK would not remain associated with Erasmus+ 2021-7 but would instead establish its own mobility programme, the Turing Scheme, available to fund student mobility across the globe for UK based students. This article considers the reasons for this decision and various features of the new scheme. Concern is expressed at the implications for collaborative work between universities of the absence of funding for students coming to the UK for study periods, and for staff mobility; on the other hand, the em- phasis on funding opportunities for disadvantage students is welcomed, as is funding for very short study periods. The position of Switzerland, no longer a full member of Erasmus since 2014, and the lessons for the UK afforded by the experience of Switzerland, are considered.